"Care from the heart": older minoritised women's perceptions of dignity in care. Issue 1 (16th March 2015) - Saltus, Roiyah; Pithara, Christalla
Abstract : Purpose: – Drawing findings from a large mixed-method study on perceptions of dignity, care expectations, and support in relation to older women from Black and minority-ethnic backgrounds, the purpose of this paper is to explore the interrelationships between life course events and the multiple roles adopted by women at different points in time that have shaped their perceptions of care and their care expectations in old age. Design/methodology/approach: – In total, 32 semi-structured interviews were undertaken, allowing for the collection of data on the participants' understanding of growing old, and the meaning and attributes of care and what care with dignity "looked and felt like". The theoretical framework is guided by a life-course approach and grounded within an intersectionality perspective. The majority of the participants were migrants. Findings: – Social markers such as ethnicity and cultural identity were found to influence the participants' understanding and expectations of care with factors such as gender identity and integration in the local community also of importance. How women felt they were perceived and "recognised" by others in their everyday lives with particular focus at the time of old age with the increased potential of loss of dignity due to declining capabilities, raised the importance of the family involvement in care provision, and perceived differences in the attributes of paid and non-paid care. The notion of "care from the heart" emerged as a key attribute of care with dignity. Care with dignity was understood as a purposeful activity, undertaken with intent to show respect and to acknowledge the participants' sense of worth and value. Practical implications: – The implications of this study are relevant in the current debate taking place at the EU level about the lived experiences of ageing migrant groups and care expectations. Originality/value: – The study highlights the importance of the social nature of dignity, how wider societal structures can impact and shape how care is understood for older women of migrant and minoritised backgrounds, and the need to explore migration and care across the life course.